ANALYSIS OF FACTORS AFFECTING DISTRIBUTION FUNDS IN A SYARIAH BANK ( CASE STUDY ON BANK SUMUT SYARIAH KCP BINJAI) - Sri Herlina; Dimas Fahreza Purba (Proceeding International Seminar of Islamic Studies, 2021)
The objectives of this study are (1). To analyze whether there is a significant influence on product facility factors on the distribution of funds at Bank Sumut Syariah KCP Binjai. (2). To analyze whether there is a significant influence on the promotion factor on the distribution of funds at Bank Sumut Syariah KCP Binjai. And (3). To analyze whether there is a significant influence on the location factor on the distribution of funds at Bank Sumut Syariah KCP Binjai. This research was conducted at Bank Sumut Syariah KCP Binjai. Address of the research location Jalan T. Amir Hamzah Binjai City. The instrument in this study is a questionnaire (questionnaire) consisting of statement items related to research variables, namely product, price, place, promotion and community decisions. The method used in this research is multiple regression analysis method. Multiple regression analysis is used to predict the size of the dependent variable using data from two or more independent variables whose size is known. The results of this study are product, promotion and location facilities at Bank Sumut Syariah KCP Binjai can be said to be good, but from the results of the R2 test which shows the value of R = 0.586 and R2 = R x R = 0.343 or 34%. From these results it proves that the 34% score obtained from the analysis results is still not satisfactory because the value obtained (close to 0). These results indicate that the product, promotion and location facilities can be said to be good, but not satisfactory. The results of the analysis can be said to be satisfactory if they are close to 100%. From the R2 test which results in 34% percentage which shows that the product facilities, promotion and location have sufficient influence on the distribution of funds, but the results of this analysis are not satisfactory. Because it only achieved 34%, this is something that must be corrected and evaluated in the coming years to improve service quality through the quality of service as an individual or person who is directly dealing with customers. Based on the t test table of 3.469 means that the variable X which is the independent variable has an effect on variable Y which is the dependent variable.Keywords: The factors that influence the distribution of funds